2020
DOI: 10.21608/zjar.2020.94485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preceding Crops and Foliar Micronutrients Applications on Yield and Yield Components of Bread Wheat Under Sandy Soil Conditions

Abstract: ASL), to evaluate the effect of fallow (control), clover and fodder maize as a preceding crops and foliar application of some micronutrients on yield and yield components of wheat cv. Gemmiza 11. The experimental design was split plot with three replications. Main plots were allocated by preceding crops and sub plots were occupied by three micronutrients salts FeSO 4 , ZnSO 4 and MnSO 4, in seven combinations of micronutrients foliar application T1: (Fe +Zn + Mn), T2: (Fe +Zn), T3: (Fe + Mn), T4: Fe, T5: (Zn +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The sequence of corn-clover-wheat produced higher grain and straw yield when compared to the sequence of corn-fallow-wheat (Gad et al, 2018). Clover as a preceding crop left a good residual effect on the wheat plant which gave the highest yield and its components compared to fodder maize and follow (Abd Allah et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The sequence of corn-clover-wheat produced higher grain and straw yield when compared to the sequence of corn-fallow-wheat (Gad et al, 2018). Clover as a preceding crop left a good residual effect on the wheat plant which gave the highest yield and its components compared to fodder maize and follow (Abd Allah et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Pagnani et al (2019) found that wheat-faba bean sequence produce the highest grain yields, due to an increased number of spikes/ m 2 , while the lowest grain yield was recorded under wheat-wheat. The superiority of grain and straw yields of wheat grown after clover may be attributed to the high values of most of yield components such as number of spikes/m2, number of grains/spike and 1000-grain weight (Abd Allah et al, 2020). Variation of wheat yield after different legume sequence could be attributed to legumes differing in the amount of biological N2 fixation.…”
Section: Vii-economic Evaluationmentioning
confidence: 99%
“…Hamdany et al (2016) indicated that the highest values of cereal units, economic evaluation, net return and improved physical and chemical properties of soil for the next planting resulted from the crop sequence corn followed by fahal berseem one cut followed by wheat compared the other treatments in both seasons. Growing wheat after soybean and clover (as legume crops) increased plant height, number of spikes m -2 , number of spikelets spike -1 , number of grains spike -1 , spike length, grain weight spike -1 , 1000-grain weight, straw yield, and grain yield (Abomarzoka & Hamadny, 2017;Gad et al, 2018;Abd Allah et al, 2020). Likewise, Andrii et al (2021) indicated that after the preceding crop soybean, wheat crop gained the maximum yield (5.77ton ha -1 ).…”
Section: Introductionmentioning
confidence: 99%